Contemporary Islamic Monetary Instruments and Their Implementation in Indonesia - Annisa Masruri Zaimsyah (PT Bukuloka Literasi Bangsa, 2025)
This paper examines contemporary Islamic monetary policy instruments implemented in Indonesia within the dual banking system framework established by Law No. 10 of 1998. Key instruments discussed include the Statutory Reserve Requirement (GWM), Mudharabah Investment Certificates among Islamic Banks (Sertifikat IMA), Bank Indonesia Sharia Certificates (SBIS), and Bank Indonesia Sharia Deposit Facilities (FASBIS), all based on Sharia contracts such as ju'alah and mudharabah that replace conventional interest-bearing instruments. The theoretical framework reviews three Islamic monetary policy schools of thought from the early Islamic period to the mainstream and alternative approaches emphasizing consultation between monetary authorities and the real sector. Empirical data from Bank Indonesia highlight the utilization and regulation of these instruments. The study concludes that the application of Islamic monetary instruments fosters monetary stability and supports the growth of the Islamic financial sector, aligning with Indonesia’s increasing demand for Sharia-compliant financial services. Keywords: Islamic monetary instruments, Sharia contracts, Bank Indonesia Syariah Certificates, statutory reserve requirement, Islamic finance, monetary stability.